IMPLEMENTASI ALGORITMA DIJKSTRA SEBAGAI SOLUSI EFEKTIF PEMBUATAN SISTEM BANTUAN BENCANA REAL TIME - Nandiroh, Siti; Haryanto, Haryanto; Munawir, Hafidh (Universitas Muhammadiyah Surakarta, 2013)
Research on communications technologies that support by Dijkstra algorithm, as a determinant of the distribution are more effective for the volunteer. The system also equipped by the data inventory and needs of each refugee, so there is no buildup and lack support in their respective refugee camps, as well as appropriate aid, according to the type of the needs of victims. This study is a system which has the purpose of making supplies, disaster relief distribution channel based on the criteria of value chain, and the level of priority areas or disaster, and disaster guide information is up to date. Information systems that are formed based on the Djikstra algorithm, while the technology which is the basis of the system is mobile. The final results will be verified by BNPB and MDMC as well as local government and police disaster area. So the information system that will form the basis for appropriate and relevant to distributed.